Referees' use of heuristics: The moderating impact of standard of competition - Souchon, N.; Cabagno, G.; Traclet, A.; Trouilloud, D.; Maio, G. (Journal of Sports Sciences, 2009)
The influence of players' standard of competition on referees' decision making was investigated. Standard of competition was examined by studying 30 handball matches, 15 at League and 15 at National standard. At both standards, we examined two types of refereeing decision (sporting and disciplinary) after transgressions that varied in ambiguity. The results indicated that referees made more lenient decisions at higher standards of competition, but this tendency depended on the type of decision being made and ambiguity in the offence. The hypothesis that referees use standard of competition as a judgemental heuristic, but in varying ways, was supported.